Management of Crohn’s disease in Taiwan: consensus guideline of the Taiwan Society of Inflammatory Bowel Disease updated in 2023 - Jia-Feng Wu; Hsu-Heng Yen; Horng-Yuan Wang; Ting-An Chang; Chung-Hsin Chang; Chen-Wang Chang; Te-Hsin Chao; Jen-Wei Chou; Yenn-Hwei Chou; Chiao-Hsiung Chuang; Wen-Hung Hsu; Tzu-Chi Hsu; et al. (Intestinal Research, 2024)
Crohn’s disease (CD) is a chronic, fluctuating inflammatory condition that primarily affects the gastrointestinal tract. Although the incidence of CD in Taiwan is lower than that in Western countries, the severity of CD presentation appears to be similar between Asia and the West. This observation indicates the urgency for devising revised guidelines tailored to the unique reimbursement system, and patient requirements in Taiwan. The core objectives of these updated guidelines include the updated treatment choices and the integration of the treat-to-target strategy into CD management, promoting the achievement of deep remission to mitigate complications and enhance the overall quality of life. Given the diversity in disease prevalence, severity, insurance policies, and access to medical treatments in Taiwan, a customized approach is imperative for formulating these guidelines. Such tailored strategies ensure that international standards are not only adapted but also optimized to local contexts. Since the inception of its initial guidelines in 2017, the Taiwan Society of Inflammatory Bowel Disease (TSIBD) has acknowledged the importance of continuous revisions for incorporating new therapeutic options and evolving disease management practices. The latest update leverages international standards and recent research findings focused on practical implementation within the Taiwanese healthcare system.